De første trykte islandske ordbøger - Ingólfsson, Gunnlaugur (Nordiske Studier i Leksikografi, 2012)
During the mid-seventeenth century two dictionaries of the Icelandic language by Icelandic scholars were compiled. One of them, Specimen Lexici Runici, was originally written by Magnús Ólafsson (†1636), priest at Laufás in Northern Iceland, the other, Lexicon Islandicum, was written by Guðmundur Andrésson (†1654), who lived in Copenhagen from 1649 until his death. Both of these works were undertaken on the initiative of the Danish professor Ole Worm (†1654), who was an ardent researcher of Danish and other Nordic antiquities. After preliminary editing, revision and additions to the original glossary, Specimen was published in Copenhagen by Worm in 1650. This work concentrates on classical Old Icelandic literature, the Eddas, sagas and skaldic poetry, with a few words and idioms, proverbs and poetry from the contemporary language of the author. The other work, Lexicon Islandicum, although completed in 1654, was not published until 1683 by PHI. Resen, professor at the University of Copenhagen. This work is considerably more comprehensive than Specimen. The basic vocabulary actually stems from Old Icelandic literature, but a host of words and phrases are taken from the author’s contemporary language, both from poetry and prose. So many expressions and idioms appear here and are explained for the first time that this work is very important for the history of Icelandic vocabulary. In the paper these works are described more closely and compared to each other.